Stakeholders, innovative business models for the circular economy and sustainable performance of firms in an emerging economy facing institutional voids - Chiappetta Jabbour, Charbel Jose; Seuring, Stefan; Lopes de Sousa Jabbour, Ana Beatriz; Jugend, Daniel [UNESP]; De Camargo Fiorini, Paula; Latan, Hengky; Izeppi, Wagner Colucci [UNESP] (Elsevier, 2020)
The literature on the diffusion of the circular economy (CE) rarely provides empirical evidence from emerging economies that face institutional voids and sustainability paradoxes. In contrast, drawing on stakeholder theory, in this paper we test a research framework capable of capturing the imbricated and complex relations among stakeholder pressure, barriers to and motivators of the CE, circular business models, and firms’ sustainable performance. Survey-based primary data was gathered from Brazilian industrial companies which lack regulatory clarity regarding the implementation of a CE. Our research results comprise both expected and unexpected outcomes: (i) differing from other countries, the relevance of regulatory stakeholders in Brazil could not be fully confirmed, adding complexity to the topic; (ii) unexpectedly, in this research, company owners/shareholders were the most salient stakeholders; (iii) stakeholders do indeed exert influence on how firms deal with barriers to and motivators of a CE; (iv) we found that internal barriers and internal motivators were perceived as more intense than external ones, which may create organizational tensions; (v) the adoption of a CE by firms tends to improve their sustainable performance; (vi) the previous possession of ISO 14001 and ISO 9001 certifications may control the way companies perceive the benefits of a CE.
Keywords: Circular economy; Stakeholders; Sustainable business models; Sustainable innovation; Sustainable performance